Pemberdayaan Usaha Mikro Kecil dan Menengah Paska Berlakunya UndangUndang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Adhi Prasetyo Satrio Wibowo (Pusat Kajian Anggaran, 2022)
The Empowerment of Micro, Small, and Medium Enterprises (MSMEs) in Act Number 11 of 2020 concerning Job Creation has amended eleven articles, added nineteen new articles, and deleted one article from three Acts. These Acts are Act Number 25 of 1992 concerning Cooperatives, Act Number 20 concerning Micro, Small, and Medium Enterprises, and Act Number 38 concerning Roads. This paper aims to find out about MSMEs' empowerment process after the enactment of the Job Creation Act and what challenges are faced by the government in MSMEs' empowerment in order to increase the level of MSME actors in Indonesia. The research method is developed using normative juridical methods through literature studies that examine primary legal materials and secondary legal materials. Furthermore, the data analysis techniques used in this study were carried out using qualitative methods, through the collection of written legal materials that were classified according to the order of the identified problems. Based on the results of the study, there are several improvements that should be made by the government related to the criteria for MSMEs, availability of a single database, MSMEs management integration, partnerships, business licensing access, facilitation of financing and fiscal incentives, Special Allocation Funds, protection and empowerment of MSMEs.